What About Me? The Importance of Teacher Social and Emotional Learning and Well-Being in the Classroom. (April 2023) - Lee, Erica O.; Lacey, Heather M.; Van Valkenburg, Sarah; McGinnis, Ellen; Huber, Brenda J.; Benner, Gregory J.; Strycker, Lisa A.
Today's teachers experience high levels of stress and fatigue that can negatively affect their well-being. Teacher burnout is not a new educational phenomenon, but it has been exacerbated by the COVID-19 pandemic. In this article, we discuss the prevalence of teacher stress and its impact on teacher well-being and student achievement. We call for more attention to the social and emotional learning of special education teachers of students with emotional and behavioral disorders. After addressing myths and misconceptions regarding current expectations for educators, we propose a new framework for establishing individual and systemic interventions to support teacher well-being.